2010
DOI: 10.1002/j.2168-9830.2010.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Classes That Click: Fast, Rich Feedback to Enhance Student Learning and Satisfaction

Abstract: BACKGROUNDOur goal is to improve student learning in foundation engineering courses.These courses are prerequisite to many higher-level courses and are comprised of critically needed concepts and skills. PURPOSE (HYPOTHESIS) We hypothesize that learning is improved by providing rapid feedback to stu dents on their understanding of key concepts and skills. Such feedback also provides students with insight into their strategies for learning. DESIGN/METHODIn two consecutive years, we conducted this study in t\… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 22 publications
1
53
0
1
Order By: Relevance
“…Students, in general, appreciate the immediate feedback provided through electronic in-class or online quizzing avenues [3,9] and instructors feel that students are better prepared for in-class reflections and discussions when they have taken an online quiz prior to the class [10]. While all researchers indicate that the addition of online modules results to improve learning outcomes compared with traditional face-to-face instruction [4,5,7,9,11], some [12] point out that weaker students are the ones mostly benefiting from online quizzes.…”
Section: Introductionmentioning
confidence: 99%
“…Students, in general, appreciate the immediate feedback provided through electronic in-class or online quizzing avenues [3,9] and instructors feel that students are better prepared for in-class reflections and discussions when they have taken an online quiz prior to the class [10]. While all researchers indicate that the addition of online modules results to improve learning outcomes compared with traditional face-to-face instruction [4,5,7,9,11], some [12] point out that weaker students are the ones mostly benefiting from online quizzes.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The proposition is that these combined activities facilitated more effective transfer of information from short-term to longterm memory, 2,21,22 and allowed students to retrieve and apply the knowledge gained in the final exams. This accounted for the significantly higher final exam averages in the ARS sections.…”
Section: Resultsmentioning
confidence: 99%
“…Since summative assessments only provide information on students understanding of domain knowledge, 1 they are ineffective in evaluating learning because they do not provide opportunities for students to apply, revise and improve the quality of their knowledge and understanding. 2 Research has shown that for students to gain insight into their learning and engage in the process of actively evaluating their current levels of understanding, they must be provided with formative assessments. [2][3] These forms of assessments are among the most effective methods of supporting student learning 1,4 and have been extensively employed in a variety of educational settings that include K-12 to higher education classes, small or large classes and in a wide array of STEM courses.…”
Section: Introductionmentioning
confidence: 99%
“…The instructor can then use the aggregated student responses to adapt instruction to address any common misconceptions. This method has been shown to improve student learning [4]- [6], especially if integrated with peer discussion.…”
Section: Existing Mastery Based Assessment Systemsmentioning
confidence: 99%